Dynamic analysis of two-link flexible manipulator considering the link length ratio and the payload - Bien, Duong Xuan; My, Chu Anh; Khoi, Phan Bui (Vietnam Journal of Mechanics, 2017)
Dynamic modeling and analysis of flexible manipulators play an essential role in optimizing mechanical design parameters and control law of real robot systems. In this paper, a nonlinear dynamic model of a manipulator is formulated based on the Finite Element Method. To analyze the dynamic behavior effectively, a numerical simulation scheme is proposed by taking full advantages of MATLAB and SIMULINK toolboxes. In this manner, the effect of varying payload and link length ratio of the manipulator to its elastic displacement is dynamically taken into account. The simulation results show that the payload and length link ratio have significant influences on the elastic displacements of the system. In particular, a proper spectrum of the link length ratio, in which the flexural displacement of the end point of the manipulator is smallest, is demonstrated. To this end, the proposed methodology could be used further to select optimal geometric parameters for the links of new robot designs.